Polymorphism of segmented grain boundaries in two-dimensional transition metal dichalcogenides - Yu, Maolin (2022)
Grain boundaries (GBs) are vital to crystal materials and their applications. Although GBs in bulk and two-dimensional materials have been extensively studied, the segmented GBs observed in transition metal dichalcogenide monolayers by a sequence of folded segments remain a mystery. We visualize the large-area distribution of the segmented GBs in MoSe2 monolayers and unravel their structural origin using ab initio calculations combined with high-resolution atomic characterizations. Unlike normal GBs in two-dimensional materials with commonly one type of dislocation cores, the segmented GBs consist of two basic elements-4|8 and 4|4|8 cores, whose alloying results in structural diversity and distinctly high stability due to relieved stress fields nearby. The defective polygons can uniquely migrate along the segmented GBs via the movement of single molybdenum atoms, unobtrusively endowing a given GB with variable appearances. Furthermore, the segmented GBs can achieve useful functionalities such as intrinsic magnetism and highly active electrocatalysis.